The Smart Glasses Using Iot And Unity (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The project is based on IOT(Internet of Things) field of Computer Science branch. The world sees the future of technology in micro sized magic boxes wherein the devices would turn into a compact thing which can be taken anywhere and used viably. Therefore  the idea of “THE SMART GLASSES”. Using Augmented Reality and ultrasonic sensors, camera, beeper and vibrator the model stands out among all the existing models by uniquely adding the idea of having “EYES AT THE BACK” where any close encounter of any person or vehicle in the personal space of the respective person leadsto direct alert through vibration and beeping.